Incidence of venous thromboembolic events in patients diagnosed with COVID-19: A literature review (Research, Society and Development, 2022)
Since the beginning of the pandemic caused by sars-cov-2, attempts have been made to elucidate the mechanism of action of the virus and its consequences in the human body. There is a relationship between the infection caused by the virus and the process of hypercoagulability, corroborating the occurrence of vascular events during the course of the disease, especially in critically ill patients. The objective of the study is to elucidate the incidence of venous vascular events through a literature review, in addition to highlighting the dynamics of the D-dimer marker in the prognosis of the disease. The methodology used for this scientific investigation was of a basic nature, with the objective of recording and describing the observed facts, adopting a qualitative approach, through a bibliographic review on different digital platforms. It was noticed that there was a high incidence of venous thromboembolism in patients diagnosed with COVID-19, being higher in patients who were in an intensive care unit. The manifestation occurred in two ways, as Deep Vein Thrombosis (DVT), which usually occurs in the lower limbs, and as Pulmonary Embolism (PE), being clots that travel through the blood circulation of the lung. The increase in the D-dimer marker was related to an indicator of poor prognosis during the course of infection. The increase was more pronounced in critically ill patients and in those who died. Therefore, questions about the incidence of VTE in patients affected by COVID-19 are scored so that, in this way, one can have a better understanding of the implications of these in the follow-up of patients.